Critical thinking efficacy and transfer at an International Baccalaureate Diploma Programme school in Finland - Horn, Shane (fi=Turun yliopisto|en=University of Turku|, 2019)
With the advent of the ‘fake news’ phenomenon providing a backdrop for relevance, this study is concerned with critical thinking (CT) efficacy and transfer, the former referring to the extent to which facilitation of CT skills meet their intended goals and the latter referring to the extent that CT may extend to external contexts such as the media literacy skills required in daily online interactions. These topics were explored by replicating tasks developed by the Stanford History Education Group (SHEG) at an International Baccalaureate Diploma Programme (IBDP) school in Finland. To further consider the extent that the IBDP may foster growth in CT skills, the tasks were administered to a ‘pre-IB’ cohort (n=42) preparing to enter the IBDP and an ‘IB2’ cohort (n=25) preparing to graduate from the IBDP. While results indicate stronger outcomes on the tasks by the IB2 comparative to the pre-IB, both cohorts in Finland outperformed the U.S. cohorts from the SHEG study (n=170-176) to a far more statistically significant degree. Utilising an existing framework of curricular approaches to facilitating CT skills development as a variable of interest for causal-comparison, it was determined that the Finnish education system and the IBDP develop CT skills by explicitly teaching CT as a separate course, whereas the curriculum guiding the participants in the SHEG study implicitly embeds CT into subject areas. Implications for increasing explicit facilitation in CT course design across curricula, professionalising CT across the field, and the benefits of replicating existing studies in differing socioeducational environments are discussed.